O ‘Programa Minha Casa, Minha Vida’: um estudo acerca da efetivação do direito à moradia digna à luz do direito à cidade e da proteção do beneficiário-consumidor - Melo Netto , Antonio Pedro de (2018)
The present work analyzes the ‘Programa Minha Casa, Minha Vida' under its capacity to promote sustainable economic and social development, while it represents a governmental intervention in the real estate market with the purpose of reducing the housing deficit, with respect to the right the city and the consumer, and thus, implementing the fundamental right to decent housing. For that, the deductive method was used as method of approach; already in relation to the objectives the applied method is descriptive and as for the technical procedure, the bibliographic and direct documentary method was used. Through this research, it was identified that the PMCMV had a small impact on the relative reduction of the housing deficit, since it could not reach the lower income population that makes up this deficit. On the contrary, the program presented dysfunction with its objectives to the one that promoted population segregation and violation of several rights related to the Right to the city. Besides this, it also promoted consumer indebtedness, imprisoned in contracts of adhesion and expelled from urban centers with debts in values greater than the value of the property acquired. Thus, it was noticed that the program did not fulfill its main objective, to effect the fundamental right to housing as the absolute deficit increased, and created new difficulties while it did not offer the necessary structure to a decent dwelling, having the program served as stimulus to economic growth.